2022
DOI: 10.3390/en15051794
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of a National and Corporate Carbon Emission Reduction Target on Renewable Electricity Use: A Review

Abstract: The Paris Agreement requires countries to propose their National Determined Contributions (NDCs) and encourages companies to engage in climate action. This two-stage study explores the mutual influence of national and corporate carbon reduction targets and their effect on the adoption of renewable energy using Hierarchical Linear Modeling (HLM). The subjects are companies nested in the G20, engaging in the Science-Based Target initiative (SBTi) or the RE100 initiative. These empirical results show corporate ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…However, the diffusion of renewable energy technologies (RETs) has been slow, and there are innovation system problems that hinder their development and diffusion in different countries (Negro et al, 2012). National and corporate carbon emission reduction targets have a non-significant impact on corporate renewable energy use, indicating that multinational corporations may perform better than national deployment on climate change (Chang & Lo, 2022;Anamu et al, 2023).…”
Section: Future Outlook and Emerging Trends Of Renewable Energy Adopt...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diffusion of renewable energy technologies (RETs) has been slow, and there are innovation system problems that hinder their development and diffusion in different countries (Negro et al, 2012). National and corporate carbon emission reduction targets have a non-significant impact on corporate renewable energy use, indicating that multinational corporations may perform better than national deployment on climate change (Chang & Lo, 2022;Anamu et al, 2023).…”
Section: Future Outlook and Emerging Trends Of Renewable Energy Adopt...mentioning
confidence: 99%
“…While the adoption of renewable energy can improve environmental performance, the economic implications of this transition remain a fundamental question for electric utilities (Ruggiero & Lehkonen, 2017). Moreover, the impact of national and corporate carbon emission reduction targets on renewable electricity use has been a subject of review, highlighting the non-significant effect of national-level targets on corporate renewable energy use (Chang & Lo, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced NDC will also provide a short-term target of emission reduction by 2030 and achieve net zero by 2060 (Ministry of Environmental and Forestry, 2022), which could be challenging for Indonesia without international support (Suroso et al, 2022). In addition to assisting in the reduction of GHG emissions, the NDC has a positive impact on encouraging sectors to shift to renewable energy (Chang and Lo, 2021). Additionally, the NDC represents pathways to decarbonization and a shift toward energy transition (Siriwardana and Nong, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that mineral enterprises, as the main body of carbon emissions, shoulder an important responsibility for emission reduction. As national policies are driven, more and more companies are moving towards low-carbon and sustainable business models [7]. Sustainable mining practices are critical to the industry's long-term health [8].…”
Section: Introductionmentioning
confidence: 99%